Congenital midline cervical cleft - Mahdi Parvizi Mashhadi; Mehdi Fathi; Mohammad Mehdi Zarif soltani; Alireza Ghodsi; Marjan Joodi (Elsevier, 2021)
Midline cervical cleft is an extremely rare congenital anomaly of the anterior neck, which accounts for 1.7-2% of congenital neck malformations. Here, we report a case of an 18-month-old boy with congenital midline cervical cleft who was successfully treated with surgical resection.